PENILAIAN KEPUASAN PELANGGAN DENGAN APLIKASI SURVEI PADA PDAM KOTA BENGKULU - Khairil Khairil (UNIB Press, 2021)
Customer satisfaction is a major reason in the service or goods business. The company will get a big profit if the customer is satisfied with the ideal service provided. The purpose of this study was to find the level of satisfaction of the PDAM's performance on customer service by making an online satisfaction survey application. The research method used is system requirements analysis, designing system requirements, coding translating the system with a programming language, implementing the system and maintaining any changes to the system. The results of the study show that the satisfaction survey application can make it easier for customers to send complaints about the service quality of PDAM Kota Bengkulu. With the PDAM polling application, it is faster to take action according to complaints from customers.